Students' Perceptions of Writing Descriptive Text at the Eighth Grade of SMP N 1 Sambi Boyolali in 2016/2017 Academic Year : Descriptive Qualitative Approach - Mustikawati, Nawang, Fitri Kurniawan, M. Res, Ed (2017)
Abstract The purpose of this research is to describe how are the perceptions of the eighth grade students of SMP N 1 Sambi Boyolali in 2016/2017 academic year on writing descriptive text. The current research uses descriptive qualitative approach. Participants of this research are two students from eighth grade of SMP N 1 Sambi Boyolali. Method of collecting data used is interview approach, while the method of data analysis is through content analysis. The results of this research are as follows: students' perception of writing descriptive text are 1) Learning descriptive text is mostly reading, writing, translating, doing exercise and completing quiz; 2) learning descriptive text is realtively doable for student; 3) learning descriptive is generally about popular topic; while the difficulties faced by students when writing descriptive text are 1) limited source of vocabulary; 2) lack of access of dictionary; 3) confusion in deciding the correct tenses; 4) unclear explanation from the teacher. Keywords : student's perception, writing, descriptive text.